Measure for Measure: Measuring the Usefulness of Measuring Antiseizure Medication Levels. Issue 3 (May 2020) - Faught, Edward
Therapeutic Drug Monitoring of Newer Antiepileptic Drugs: A Randomized Trial for Dosage Adjustment Aícua-Rapún I, André P, Rossetti AO, et al . Ann Neurol. 2020;87(1):22-29. doi:10.1002/ana.25641 . Objective: Therapeutic drug monitoring (TDM) of antiepileptic drugs (AEDs) is widely established for older generation AEDs, whereas there is limited evidence about newer AEDs. Our aim is to assess the benefit of TDM of newer generation AEDs in epilepsy. Methods: We performed a randomized, controlled trial comparing systematic with rescue TDM of lamotrigine, levetiracetam, oxcarbazepine, topiramate, brivaracetam, zonisamide, or pregabalin. Participants were adults with epilepsy, in whom treatment with newer generation AEDs was initiated or needed adjustment. In the systematic TDM arm, AED plasma levels were available at each appointment, whereas in the rescue TDM arm, levels were known only if a study end point was reached (inefficacy or adverse events). The primary outcome was the proportion of participants who followed 1 year without reaching one of the predefined end points. Results: A total of 151 participants were enrolled; global retention in the study was similar in both arms (56% overall, 58% in the systematic, and 53% in the rescue TDM arm, P = .6, Cox regression). There was no difference in terms of outcome regarding treatment efficacy or tolerability. Partial adherence of clinicians to TDM (adjusting or not AED dosage based on blood levels) did not explain this lack of benefit. Interpretation: This study provides class A evidence that systematic drug-level monitoring of newer generation AEDs does not bring tangible benefits in the management of patients with epilepsy. Poor correlation between clinical effects and drug levels likely accounts for this finding. However, TDM is useful in several situations, such as pregnancy, as well as when there are compliance issues.